A clinical conundrum: the detrimental effect of TNF antagonists in multiple sclerosis. - Dendrou, C; Bell, J; Fugger, L (2013)
Although TNF antagonists are efficacious in treating a range of autoimmune conditions, they exacerbate or even promote multiple sclerosis (MS)--a clinical finding that has been a conundrum for over a decade and has been a source of debate regarding the role of these drugs and of TNF signaling in the development of demyelinating disease. Recent work investigating the functional consequences of MS-associated genetic variation in the gene encoding TNFR1 has demonstrated that genetic risk drives the production of a novel, endogenous TNF antagonist. This mirrors the clinical experience with the drugs and indicates that the net effect of TNF function in MS development is a protective one, warranting a re-evaluation of the studies that have contributed to our understanding of TNF signaling in inflammation, immunoregulation and neuroprotection, to determine how future research can be directed towards targeting this pathway for therapeutic benefit.